Effect of sprint interval training on circulatory function during exercise in sedentary, overweight/obese women - Trilk, Jennifer L.; Singhal, Arpit; Bigelman, Kevin A.; Cureton, Kirk J. (European journal of applied physiology, 2011)
Very high-intensity, low-volume, sprint interval training (SIT) increases muscle oxidative capacity and may increase maximal oxygen uptake ( ), but whether circulatory function is improved, and whether SIT is feasible in overweight/obese women is unknown. To examine the effects of SIT on and circulatory function in sedentary, overweight/obese women. Twenty-eight women with BMI > 25 were randomly assigned to SIT or control (CON) groups. One week before pre-testing, subjects were familarized to testing and the workload that elicited 50% was calculated. Pre- and post-intervention, circulatory function was measured at 50% of the pre-intervention , and a GXT was performed to determine . During the intervention, SIT training was given for 3 days/week for 4 weeks. Training consisted of 4–7, 30-s sprints on a stationary cycle (5% body mass as resistance) with 4 min active recovery between sprints. CON maintained baseline physical activity. Post-intervention, heart rate (HR) was significantly lower and stroke volume (SV) significantly higher in SIT (−8.1 and 11.4%, respectively; P < 0.05) during cycling at 50% ; changes in CON were not significant (3 and −4%, respectively). Changes in cardiac output ( ) and arteriovenous oxygen content difference [(a − v)O 2 diff] were not significantly different for SIT or CON. The increase in by SIT was significantly greater than by CON (12 vs. −1%). Changes by SIT and CON in HR max (−1 vs. −1%) were not significantly different. Four weeks of SIT improve circulatory function during submaximal exercise and increases in sedentary, overweight/obese women.